Outliving and outlasting: explaining sex inequities in healthy life expectancy through the lens of multimorbidity and within morbidities in older populations in India - Kumar, Ajay (Frontiers in Public Health, 2025)
BackgroundLife expectancy (LE) at birth in India has increased substantially over the past century, initially driven by reductions in infant and childhood mortality and later supported by declining mortality in older population. Despite these gains, sex gaps in LE have widened, and healthy life expectancy (HLE) has declined, largely due to escalating non-communicable diseases (NCDs) and, more recently, a growing burden of multimorbidity among older adults.DataUsing the Sample Registration System (SRS) and nationally representative Longitudinal Ageing Study in India (LASI) Wave 1, we assessed sex-specific patterns in healthy lifespan inequality (HLI), decomposed disparities in HLE, and quantified inequality arising from mortality and the prevalence of multimorbidity/complex multimorbidity.ResultsFemales have a marginal advantage in HLE (30.59 years) compared to males (29.15 years) and have higher multimorbidity-free life expectancy (25.50 years vs. 23.30 years). However, they also live longer with multimorbidity (6.09 years vs. 5.85 years) and spend significantly more time with complex multimorbidity (10.77 years vs. 8.93 years). Mortality differentials remain the dominant contributor to sex-specific HLE gaps. Disease- and multimorbidity-specific patterns reveal a survival–morbidity paradox: women live longer than men but accumulate a greater burden of diseases and conditions. Moreover, cardiovascular and musculoskeletal diseases account for significant losses in disease-free life expectancy (DFLE) among women, while men experience steeper declines due to respiratory diseases.ConclusionAs India undergoes demographic ageing and an epidemiological shift toward chronic disease dominance, reducing sex disparities in HLE requires targeted public health strategies. Prioritizing prevention, early detection, and integrated management of multimorbidity particularly complex multimorbidity among older women will be essential to narrow the growing gap and promote healthier ageing.